2019
DOI: 10.1177/0748233719885574
|View full text |Cite
|
Sign up to set email alerts
|

In vitro application of sodium arsenite to mice testicular and epididymal organ cultures induces oxidative, biochemical, hormonal, and genotoxic stress

Abstract: Arsenic poisoning is well-known for its innumerable toxic and carcinogenic effects. In vivo data on reproductive toxicity are also known but in vitro data are scant. Presently, we evaluated the in vitro toxic effects of sodium arsenite (NaAsO2) on adult mice testes and epididymal tissues using organ cultures. Testicular and epididymal fragments were incubated at 37°C and 33°C, respectively, with 1, 10, 50, and 100 µM concentrations of NaAsO2. Cultures were allowed to incubate for 2 and 24 h. Levels of oxidativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
(40 reference statements)
0
5
0
Order By: Relevance
“…In the Leydig and Sertoli cells of mice testes, exposure to sodium arsenite at concentrations of 50 and 1000 ppb for 24, 48, and 72 h caused cytotoxicity and impaired antioxidant systems [144]. In vitro cell cultures of rodent testes and epididymis treated with sodium arsenite at concentrations of 1, 10, 50, and 100 µM for 2 and 24 h increased ROS, TBARS, and sperm DNA damage, decreased catalase, peroxidase, and superoxide dismutase, and decreased serum testosterone [157]. Sodium arsenite at a dose of 10 mg/L through drinking water was shown to induce overexpression of SOD1, CAT, GSTK1, and MT1 in the testes and epididymis of rats [148].…”
Section: Arsenic-induced Oxidative Stressmentioning
confidence: 98%
See 1 more Smart Citation
“…In the Leydig and Sertoli cells of mice testes, exposure to sodium arsenite at concentrations of 50 and 1000 ppb for 24, 48, and 72 h caused cytotoxicity and impaired antioxidant systems [144]. In vitro cell cultures of rodent testes and epididymis treated with sodium arsenite at concentrations of 1, 10, 50, and 100 µM for 2 and 24 h increased ROS, TBARS, and sperm DNA damage, decreased catalase, peroxidase, and superoxide dismutase, and decreased serum testosterone [157]. Sodium arsenite at a dose of 10 mg/L through drinking water was shown to induce overexpression of SOD1, CAT, GSTK1, and MT1 in the testes and epididymis of rats [148].…”
Section: Arsenic-induced Oxidative Stressmentioning
confidence: 98%
“…A case study conducted with Unexplained Recurrent Spontaneous Abortion (URSA) patients at Beijing Maternal and Child Health Care Hospital found an increased level of arsenic in the blood, which suggests that blood arsenic may increase the risk of URSA in women of childbearing age [165]. A cohort study of 205 pregnant women in Hanam province, Vietnam revealed that prenatal exposure to drinking water containing high levels of arsenic showed increased cord arsenic levels, 8-OHdG, 8-nitroguanine, DNA strand break, and MN frequency, illustrating the genotoxic effects of arsenic [157]. Low levels of arsenic exposure during pregnancy showed maternal and neonatal thyrotoxicity [166].…”
Section: Effects Of Prenatal Exposure To Arsenic In Humansmentioning
confidence: 99%
“…We used sodium arsenite (NaAsO 2 ), an inorganic compound known to induce oxidative damage in insects and other model systems, as a positive control, to estimate a scale of perturbation in protein carbonylation and GST specific activity by different treatments in the mosquitoes. In this group, the cotton pads soaked with 10% sucrose solution that was used for sugar feeding the mosquitoes was spiked with 50μM NaAsO 2 The concentration to be used for the experiments was decided after testing groups of mosquitoes with 100uM and 50uM NaAsO2 based on previous published data [ 32 ]. At 100uM, we observed complete mortality within 48 hours whereas at 50uM, the mosquitoes survived for atleast 72 hours.…”
Section: Resultsmentioning
confidence: 99%
“…2.9.2 | Oxidative stress biomarkers, antioxidant enzymes and non-enzymatic GSH Testicular homogenates were prepared according to the methods as described (Anwar & Qureshi, 2019), for the assessment of reactive oxygen species (ROS) and lipid peroxidation (TBARS), levels of reduced glutathione (GSH) and antioxidant enzymes, the superoxide dismutase (SOD), peroxidase (POD) and catalase (CAT).…”
Section: Homogenate Preparationmentioning
confidence: 99%
“…Deleterious effects of sodium arsenite (NaAsO 2 ) on testicular and epididymal organ cultures in mice have been recently documented. These include increased ROS levels, decreased antioxidant enzyme levels, decreased blood testosterone concentration and excessive sperm DNA damage, particularly at slightly high concentrations (50 and 100 µM) (Anwar & Qureshi, 2019). In addition, dose-dependent induction of apoptosis and germ cell loss were also reported in postnatal day 5 CD1 mouse testes exposed to arsenic (Anwar et al, 2020).…”
mentioning
confidence: 96%